تحليل إحتياجات المواد التعليمية الإفتراضية لمهارة القراءة - Ali Ba'ul Chusna; Uril Bahruddin (Muslim Heritage, 2022)
AAbstractReading is one of the activities to improve human knowledge. And it is one of the four Arabic language skills wich must be learned by the students. Today, reading materials represent a wide range of knowledge. Before preparing the materials of reading skill, its important to appropriate it with the required teaching objectives and students need in the teaching process. This study aims to describe the reality of online reading learning at the university level and analyzing student needs for online teaching materials in online reading learning. This research was conducted at the Department of Arabic Language Education IAIN Ponorogo. Research data obtained through observation, interviews, and questionnaires. Data analysis was carried out using a quantitative descriptive approach. The results of the study show that online learning of reading skill at the Department of Arabic Language Education IAIN Ponorogo is currently carried out by using zoom media, google classroom, and google meet. However, the fact is that learning has not been able to meet the learning objectives that have been set. The students really need online teaching materials for learning reading skills. There are six things that must be considered by the compiler as needed by students, there are instructions for use, learning objectives, supporting pictures, vocabularies, various kinds of exercises, and easy access to teaching materials.   الملخصالقراءة هي احدى الأنشطة لترقية المعرفة والعلوم عند الناس وهي من المهارة اللغوية العربية الأربعة. تمثل المواد المقروءة بابا واسعا من أبواب المعرفة اليوم. فإعداد المواد التعليمية لمهارة القراءة المناسبة بأهداف التعليم المطلوبة أمر مهم عند المؤسسة التعليمية. والتعريف على الأمور التي يحتاجها الطلبة في عملية التعليم يكون شيئا ضروريا قبل إعداد المواد التعليمية. تهدف هذه الدراسة إلى كشف أمرين هامين. أولا، وصف واقع تعليم القراءة الإفتراضي بقسم تعليم اللغة العربية بجامعة فونوروجو الاسلامية الحكومية. و ثانيا، المواد التعليمية الإفتراضية لمادة القراءة التي يحتاجها طلبة قسم تعليم اللغة العربية بجامعة فونوروجو الاسلامية الحكومية. و الطريقة التي يستعملها الباحث للحصول على البيانات المطلوبة هي طريقة الملاحظة والمقابلة و الاستبانة. ويتم تحليل البيانات بالتحليل الوصفي الكمي. و من نتيجة هذه الدراسة هي أن تعليم القراءة بقسم تعليم اللغة العربية في عصر جائحة كوفيد-19 يكون إفتراضيا باستخدام الوسائل التعليمية الإفتراضية كجوجل كلاسروم و الزوم. ولكن الواقع يكون التعليم قليل الموافقة بأهداف التعليم المطلوبة يواجه المدرس والطلبة بعض المشكلات، منها المشكلة المتعلقة  بالمواد التعليمية. ثانيا، تكون المواد التعليمية الإفتراضية شيئا محتاجا ضروريا عند الطلبة و كذلك المدرس أثناء تعليم القراءة الإفتراضي في عصر جائحة كوفيد-19 اليوم. وهناك ستة أمور لابد أن تكون بهذه المواد التعليمية الافتراضية كما يحتاجها الطلبة، وهي دليل الاستخدام وأهداف التعليم والمفردات والصورة والتدريبات وسهولة الوصول نحو المادة